PROTOTYPE SISTEM PALANG PINTU KERETA API MENGGUNAKAN INTERNET OF THINGS DAN ULTRASONIK - Sadi, Sumardi; Lenni, Lenni; Pujiono, Arif (University of Muhammadiyah Tangerang, 2024)
A train gate system based on the Internet of Things (IoT) and ultrasonic technology is proposed to improve safety and operational efficiency at railway crossings. The research background involves the safety challenges faced by conventional doorstop systems, the limitations of remote access, and the need to utilize the latest technology. This solution utilizes ultrasonic sensors to accurately detect the proximity of trains, while integration with an IoT platform enables real-time monitoring and control. The ultrasonic sensor will detect the train by giving Trigger On to the Servo to automatically close the crossing lane for public vehicle drivers, then the infrared sensor will detect the presence of a train by sending a notification to the LCDi2c to display a warning that a train will pass and at the same time will activate the Buzzerto increase security. on thistrain cross system. Then if all sensor systemsfail to close the bar, the Blynk IoT platform can be used to control wirelessly or remotely. By activating the widget on the blynk platform and all processes are managed on the Esp8266 as the controller board.